The Influence of Emotional Intelligence and Competence on Employee Performance at PT. XYZ - Hidayat, Cepi; Mulyani, Sri; Army, Widya Lilisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine and analyze the influence of emotional intelligence and competence on employee performance. Employee performance is crucial to achieving company goals, so it is important to manage human resources well, especially individuals' ability to manage their feelings and work capabilities. This study uses a quantitative method with a descriptive and verificative approach. Data was obtained from questionnaires distributed to 50 employees as research samples. Data analysis techniques included validity and reliability tests, multiple linear regression, t-tests, F-tests, and determination coefficients using SPSS software. The results showed that emotional intelligence had a positive and significant effect on employee performance. Competence also has a positive and significant effect on employee performance. When viewed together, emotional intelligence and competence have a significant effect on employee performance. These results indicate that the better the emotional intelligence and competence of employees, the higher their performance. Therefore, companies are encouraged to improve training and development of emotional intelligence and competence to support optimal improvement in employee performance.